Hong Kong Med J 2019
DOI: 10.12809/hkmj197903
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of respiratory syncytial virus infection and its effect on children with heart disease in Hong Kong: a multicentre review

Abstract: C M E disease. Predictors of severe RSV infection in patients with heart disease were heart failure, pulmonary hypertension, and severe airway abnormalities associated with congenital heart disease. Conclusions: Respiratory syncytial virus infection occurs mainly in spring and summer in Hong Kong, and is related to meteorological conditions. Respiratory syncytial virus infection poses a heavy disease burden on children with heart disease. A local guideline on RSV immunoprophylaxis for these children is therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In a multicenter review on the epidemiology of respiratory syncytial virus infection and its effect on children with heart disease in Hong Kong, KD is noted to be a complication. 9 In a recent pandemic of coronavirus infection, severe Kawasaki-like disease is associated. Pediatric multisystem inflammatory syndrome (PMIS), or multisystem-inflammatory syndrome-in-children (MIS-C), or pediatric inflammatory multisystem syndrome-temporally associated with severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) (PIM-TS) are newly coined acronynms representing a systemic disease involving persistent fever, inflammation, and organ dysfunction following exposure to SARS-CoV-2, the virus responsible for coronavirus disease 2019 (COVID-19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a multicenter review on the epidemiology of respiratory syncytial virus infection and its effect on children with heart disease in Hong Kong, KD is noted to be a complication. 9 In a recent pandemic of coronavirus infection, severe Kawasaki-like disease is associated. Pediatric multisystem inflammatory syndrome (PMIS), or multisystem-inflammatory syndrome-in-children (MIS-C), or pediatric inflammatory multisystem syndrome-temporally associated with severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) (PIM-TS) are newly coined acronynms representing a systemic disease involving persistent fever, inflammation, and organ dysfunction following exposure to SARS-CoV-2, the virus responsible for coronavirus disease 2019 (COVID-19).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, SARS-CoV-2 is just one of the many respiratory viruses that can cause MIS-C or PIMS-TS or KD. 4 , 9 …”
Section: Discussionmentioning
confidence: 99%
“…To the Editor-We refer to the multicentre review in Hong Kong Medical Journal about respiratory syncytial virus (RSV) and children with heart disease in Hong Kong. 1 There is no universal guideline in Hong Kong regarding RSV immunoprophylaxis for children with heart disease because of a lack of local data on RSV infection. The authors found predictors of severe RSV infection in patients with heart disease were heart failure, pulmonary hypertension, and severe airway abnormalities associated with congenital heart disease, and conclude RSV infection poses a heavy disease burden on children with heart disease.…”
mentioning
confidence: 99%
“…Noonan syndrome is an autosomal dominant genetic disorder that may present with mildly unusual facial features, short height and skeletal malformations, and a very common syndromic cause of congenital heart disease, including pulmonary valvular stenosis, atrial septal defects, ventricular septal defects and hypertrophic cardiomyopathy. 1,3,4 The mother also had Noonan syndrome and hypertrophic obstructive cardiomyopathy. Children aged ≤12 months with haemodynamically significant cardiomyopathy are at a higher risk for RSV infections and may benefit from palivizumab prophylaxis.…”
mentioning
confidence: 99%
“…1 With infection, cardiac function may deteriorate in children with congenital heart disease. 2 Therefore, point-of-care echocardiography should be performed in patients suffering from respiratory distress or respiratory tract infection with an identified pathogenic microorganism, especially if they have a history of heart disease.…”
mentioning
confidence: 99%